NEW APPROACHES TO THE TREATMENT OF DIABETES MELLITUS OF TYPE 2 - Боцюрко, В. І.; Марусин, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article provides an analytical review of substantiating the usage of antidiabetic medication of new class – thiazolidondion for peroral therapy of diabetes mellitus of type 2. Unlike metformin, which also reduces insulin resistance, glitazones are agonists of intranuclear receptors which are located in the cellules of adipose tissue, liver, sceletal muscles and their activation leads to the change in the activity of genes, which produce a lot of metabolically active substances. The latter actively participate in glucose and lipid metabolism, reducing their concentration in blood.